(untitled) (Journal of Hama University, 2021)
Resesearch and experimental study have been conducted to evaluate the influence of the recycled aggregates on the several mechanical properties ofrecyclied aggregate concrete(RAC), specially studying the elastic modulas. Natural aggregates were replaced by several ratios of recycled aggregates (0%, 50%, 75%, and 100%).Three cases were tested. The first case,the cement is not added or replaced by natural pozzolana. The second case, 15% of cement’s weight is replaced by natural pozzolana. The third one,adding the natural Pozzolana which is equal to 15% of cement’s weight.The studyfinidings showed that the modulus of elasticity decreases as the recycled aggregates increase. In addition, using of 15% of pozzolana as an additive with 50% of recyclied aggregate (RA)showed an improvement incompressione strength and modulus of elasticity, especially at the age of 120 days. Whereas, the recycled aggregate concrete strength was approximately equal to 97% and 103% of the natural aggregate concrete in both 28 and 120 days respectively.